Comparing Myopic Progression in Urban and Rural Junior High School in Yogyakarta - Widya Prafitri Rasmiyati; Suhardjo Suhardjo; Angela Nurini Agni (Majalah Oftalmologi Indonesia, 2016)
Background: To compare myopic progression rates in junior high school in Yogyakarta betweenurban and rural areas.Methods: A school-based survey was initially conducted. Five junior high schools were selected inboth urban and rural areas. A longitudinal follow up study was conducted 1 year later. Age range from12 to 15 years old. The refractive state of each student was measured with autorefractometer.Results: A total of 195 junior high school children participated in the study. One hundred and ninteenchildren were from urban area and 76 children came from rural area. A follow up study after 1 year,mean myopic progression in junior high school in urban area was around 0.5 D/year faster than in rural,which was 0.37 D/year. There were statistically significant difference in nearwork activities betweenchildren in urban and rural areas, with p=<0.001. Risk factor such as gender and myop status of parentsdid not relate with myop progression, only age and sosioeconomic had significant effect into the myopprogression. Mean myopic progression in junior high school children (age 12-15) in the urban area wasaround -0.50 D/year. The average progression rate was fastest in 14 years old.Conclusion: There is significant difference in increasing of myop progression between junior highschool children in urban and rural areas. This difference may be related to difference of nearworkactivities between children in urban and rural areas.Â Keywords: myopia, urban, rural, myop progression, junior high school